The Role of Driving Teachers in Educational Transformation: Learning Leadership and Innovation in Indonesian Schools - Basman, Basman; Rasid, Rasid; Yusuf Deluma, Ridwan; Fatmawati, Titi; Mujiati, Mujiati (Magister Administrasi Pendidikan, Universitas Muhammadiyah Kendari, 2025)
Improving educational quality requires systematic learning innovation, teacher empowerment, and effective leadership at the school level. This study examines the role of Driving Teachers (Guru Penggerak) in fostering educational transformation through learning leadership, professional collaboration, and community engagement in North Kolaka, Indonesia. Employing a descriptive qualitative design with a phenomenological approach, data were collected through in-depth interviews with key participants involved in the Driving Teacher program. The data were analyzed using thematic analysis to identify core themes reflecting participants’ lived experiences and perceptions. The findings reveal that Driving Teachers play a strategic role in shaping the Pancasila Student Profile through four key dimensions: learning leadership, self-development, student-centered learning, and instructional innovation. These roles are reflected in the development of students’ faith and piety, noble character, global diversity awareness, mutual cooperation, independence, and critical and creative thinking. Additionally, Driving Teachers contribute to improving teacher competence, enhancing student learning outcomes, and cultivating a collaborative school culture involving parents and the wider community.